2021
DOI: 10.1210/clinem/dgaa965
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Presentation of Pheochromocytoma and Sympathetic Paraganglioma: A Population-based Study

Abstract: Context Pheochromocytoma and sympathetic paraganglioma (PPGL) are rare catecholamine-secreting tumors but recent studies suggest increasing incidence. Traditionally, PPGL are described to present with paroxysmal symptoms and hypertension, but existing data on clinical presentation of PPGL come from referral centers. Objective We aimed to describe time trends in clinical presentation and incidence of PPGL in a population-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 20 publications
5
51
2
6
Order By: Relevance
“…As the presented data illustrate, incidental findings on imaging constitute an increasing challenge in everyday clinical practice. It has been shown that neuroendocrine incidentalomas originating from areas such as the pituitary gland, adrenal medulla or appendix seem to have a more indolent behavior compared to the symptomatic ones of the same primary site [8,25,26]. In contrast to these findings, our data show that incidental discovered siNETs seem to have a phenotype comparable to the symptomatic discovered disease.…”
Section: Discussioncontrasting
confidence: 96%
“…As the presented data illustrate, incidental findings on imaging constitute an increasing challenge in everyday clinical practice. It has been shown that neuroendocrine incidentalomas originating from areas such as the pituitary gland, adrenal medulla or appendix seem to have a more indolent behavior compared to the symptomatic ones of the same primary site [8,25,26]. In contrast to these findings, our data show that incidental discovered siNETs seem to have a phenotype comparable to the symptomatic discovered disease.…”
Section: Discussioncontrasting
confidence: 96%
“…Currently, we only have some expert opinions suggesting that patients with poorly controlled diabetes or complicated controlled diabetes and hypertension, as well as patients with unexplainable bone fragility or severe osteoporosis, should be screened for hypercortisolism (2,30,31). Consistent with the hypothesis of a current underestimation of the number of patients with adrenal diseases, the incidence of paraganglioma (PGL) has increased 4.8 times from 1977 to 2015, which is likely due to its recognition in patients with PGL found in small incidentally discovered adrenal masses and few or no paroxysmal symptoms (22). This finding suggests that current guidelines, based on old data, may not be adequate to detect patients with PGL seen in daily clinical care today.…”
Section: When To Suspect and Who To Screen For Adrenal Diseasesmentioning
confidence: 94%
“…Thus, optimizing the accuracy of screening tests has been advocated in order to avoid overdiagnosing and to individuate true positive cases. In this sense, recent findings that various adrenal disorders have a genetic basis and that genetic variants may predispose to the development of these diseases could lead to a better focus on providing screening tests to the individuals at risk (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally considered a “one in a million” disease, PPGLs have shown a rising incidence during the last 40 years, from 1.4 per million person-years in 1977 to 6.6 in 2015, constituting a 4.8-fold increase [ 6 ]. The upsurge is largely attributable to smaller tumors in patients with few/no symptoms, suggesting that an intensified use of clinical imaging techniques might contribute to this increase.…”
Section: Introductionmentioning
confidence: 99%